Functional dependence of excitation energy for pentacene/C60 model complex in the nonempirically tuned long‐range corrected density functional theory. Issue 3 (23rd February 2012) - Minami, Takuya; Ito, Soichi; Nakano, Masayoshi; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; Brändas, Erkki J.
Abstract Functional dependence of excitation energy has been investigated for pentacene/C60 model complex in the time‐dependent long‐range corrected (LC) density functional theory (TD‐DFT). We especially evaluate the performance of nonempirically tuned LC‐DFT, in which the range‐separating parameter is optimized so as to satisfy the exact condition of DFT. In addition, the effect of short‐range Hartree–Fock (HF) exchange term is also examined based on the Coulomb‐attenuating method (CAM). We have shown that the nonempirical tuning scheme improves the excitation energies by the LC‐DFT (LC‐BLYP, LC‐ωPBE, and ωB97), as well as by the CAM‐DFT (CAM‐BLYP, CAM‐ωPBE, and CAM‐ωB97), independent of the existence of short‐range HF exchange term. We have also found that the functional dependence of excitation energy is very small when the nonempirically tuned parameter is applied. This indicates that the tuning of the range‐separating parameter is essential for improving the excitation energy within the framework of the TD‐LC‐DFT. © 2012 Wiley Periodicals, Inc.